Analisis Faktor Yang Mempengaruhi Persepsi Tentang Kondom Pada Kalangan Pria Beresiko Di Malang Jawa Timur - Karisma, Riski Candra; Shaluhiyah, Zahroh; BM, Syamsulhuda (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2017)
Background: Negative perception about condoms would cause preventing HIVAIDS behavior among men that risked will be low.The cohering of condoms perception in society caused by a social factor (external), personal factors (internal) as well as a combination of both. This study aims to know the perception were the condoms that there are among the risked man in Malang East Java and the factors that influence the perceptions itself.Method: Kind of this research is explanatory research with the cross sectional approach. Respondents in this research was man with the risk that come from four kinds of work that is a truck driver, cab drivers, factory workers people and fishermen, people with the number of respondents 350. Data analysis using univariat technique, bivariat by this chi-square multivariate and techniques with the logistic regression.Results: The research result show that there is 11 variable that has been analyze, there are 8 statistically variable are associated with the perception of condoms, the age variables, education, work, marital status, respondents experience about condoms, the attitude of respondents about condoms, media information, experience others about condoms and socialization health workers. Based on the results of the multivariate stated that that is together impact on perception among the man condoms that risked in Malang is in marital status. KPA Malang districtÂ should provide detailed and easily accessible information about condoms for men who are at risk, including demonstration use.Keywords: Perception, Condom, High Man risked